Retracted: Knowledge and practices of delivery room midwives on delayed umbilical cord clamping time: a descriptive study from Turkey - Deniz Akyildiz; Sena Dilek Aksoy (Faculty of Medicine, Universitas Andalas, 2022)
This study aimed to evaluate the knowledge and practices of delivery room midwives on delayed umbilical cord clamping (DCC). This descriptive study was conducted with a total of 1,274 delivery room midwives from five regions of Turkey. The data were collected using a Google survey form. Most of the midwives defined DCC as clamping the umbilical cord in term newborns after cessation of pulsations (47.2%), and as clamping the umbilical cord in preterm newborns within 15-30 seconds of birth (31.2%). Their highest DCC time ranged between 0-10 seconds for term and preterm newborns (34.7% and 54.8%, respectively). The rates of applying DCC were 17.6% and 5.3% in term and preterm newborns, respectively. Dealing with the mother (75.6% and 33.4%, respectively), having workload (27.5% and 24.6%, respectively), considering that the newborn would have respiratory distress (16.1% and 33.4%), considering that the newborn would get cold (10.7% and 13.9%, respectively), preventing polycythemia and hyperbilirubinemia (6.7% and 9.7%, respectively), and being afraid of dropping the newborn (5.3% and 19%, 8, respectively) are the most common reasons for midwives not to apply DCC to term and preterm newborns. The majority of the midwives reported that they had no DCC protocol in their institution (80.5%) and did not receive in-service training on DCC (76.5%). This study has concluded that most midwives do not know the correct definition of DCC, do not apply DCC correctly, have quite short DCC times, have no DCC protocol in their institutions and do not receive in-service training on DCC. This article is retracted as requested by the authors. The retraction information is in volume 8, issue 1, 2023. - link